2010
DOI: 10.1007/s13197-010-0150-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of storage conditions on microbiological and physicochemical quality of shea butter

Abstract: Storage conditions are key constraints for quality assurance of the shea (Vitellaria paradoxa Gaertner) butter. In the Sudan savannah Africa, storage conditions of butter produced by women vary across and among processors, traders and consumers. These conditions could impact the quality of the products and reduced their access to international market. The present study attempted to investigate the effect of storage duration and packaging materials on microbiological and physicochemical characteristics of shea … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 9 publications
(9 reference statements)
4
18
0
Order By: Relevance
“…As observed by Honfo et al, (2011), peroxide value and iodine value also increased with days. Deterioration could also be due to invasion by microbial contaminants as reported by Esiegbuya et al (2014).…”
Section: Resultssupporting
confidence: 56%
See 3 more Smart Citations
“…As observed by Honfo et al, (2011), peroxide value and iodine value also increased with days. Deterioration could also be due to invasion by microbial contaminants as reported by Esiegbuya et al (2014).…”
Section: Resultssupporting
confidence: 56%
“…These groups of fungal species were also isolated during the course of this study. This could have been as a result of the storage duration or storage materials used in packaging the Shea butter, affirming Honfo et al (2011) who observed that increase in microbial load of the Shea butter increases with storage duration and the nature of package materials. Esiegbuya et al (2014) revealed that microbial contaminants caused colour deterioration and tainting of the Shea nut and kernel.…”
Section: Resultssupporting
confidence: 54%
See 2 more Smart Citations
“…Peanut is an important product in rural areas of Benin (Elisha, 2004;Ediage et al, 2011;Egal et al, 2005;Honfo et al, 2010). Be it in Benin, in Senegal or in Nigeria, groundnuts provide cheap protein source.…”
Section: Introductionmentioning
confidence: 99%